From the High North to the Low South: bipolar Norway's Antarctic strategy. Issue 2 (2nd July 2016) - Jensen, Leif Christian
Abstract: Based on a close analysis of the Norwegian Antarctic strategy from 2015, this article seeks to introduce Norway's main interests and political priorities concerning the Antarctic to an international audience. It should also function as an important contribution to the international relations literature on the region. This article fills out and enriches recent analyses and presentations of old and emerging positions on the Antarctic. Norway is the only truly bipolar state, the only one with territorial claims to areas in both the Arctic and the Antarctic. The first Norwegian Antarctic strategy in nearly 80 years must be read as a clear signal of intent from the Norwegian Government. It is uncommonly comprehensive and detailed, and covers most if not all of Norway's key foreign policy interests. The similarity to the Norwegian Arctic approach is rather striking. The take-home message is really that one can get a very good idea of how Norwegian foreign policy towards the Antarctic will be like by looking at Norway's previous policies and actions in the Arctic. There is a clear signal from the government that Norway's Antarctic competence and experience shall create synergies in the pursuit of national interests in the Antarctic. Norway needs a stage for its foreign policy, and new territories to promote national interests and support the national economy now that the fossil-driven Norwegian fairy tale is approaching its last chapters.